Linguistic Features and Grammatical Error Patterns in Indonesian Vocational EFL Students' Recount Writing - Aditya Ramadhan; Havid Ardi (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2026)
Recount writing requires learners to construct coherent narratives while accurately controlling grammatical features, particularly tense and cohesion. However, vocational EFL learners often experience persistent grammatical challenges that affect narrative clarity, indicating a gap between their ability to organize texts and maintain grammatical consistency. This study examines linguistic features and grammatical error patterns in recount texts written by Indonesian vocational diploma EFL students. Using a descriptive quantitative design, data were collected from 20 second-semester students through a writing task and analyzed using analytic rubrics. The analysis focused on key linguistic features (past tense, first-person pronouns, and time connectives) and ten categories of grammatical errors. The findings show that students demonstrate strong control of discourse-level features, particularly first-person pronouns (90%) and time connectives (95%), but limited mastery of past tense usage, with only 15% achieving an excellent level. Tense-related errors were the most dominant (28%), frequently disrupting narrative coherence. These results indicate an imbalance between discourse competence and grammatical accuracy. By integrating Error Analysis and the Genre-Based Approach, this study provides a more comprehensive account of EFL writing development in vocational contexts. Pedagogically, it highlights the need for integrating form-focused instruction within genre-based writing to improve grammatical consistency.